A review of power and energy management strategies in electric vehicles - Tan, Chee Wei (2012)
This paper reviews state-of-art on power and energy management strategies in hybrid electric vehicle and fully electric vehicle. Generally, there are two layer control strategies, namely the low level component control and the high level supervisory control. Management and control strategy of electric vehicles require careful design considerations because it involves multiple energy sources and storage. This would ensure that the energy storage system is managed and used at the optimum level which would ultimately contribute to system cost reduction. The overall electric vehicle performance and fuel efficiency is typically controlled by high level supervisory control algorithm that consists of event-based or time-based conditions. In short, the management of sources and control strategies used in electric vehicles should also take into account other associated factors, such as the vehicle size, purpose, operation area of vehicle, environment and weather.